Jurnalisme Profesional Pilar Demokrasi?: Analisis Kritis Perspektif Anthony Giddens - Ahmad Alwajih (Jurnal Komunikasi, 2012)
Many scholars believe that professional journalism is independence structure, so it plays importance role in democracy process. However, this notion is inadequate. There are critics came from the scholars who thought that journalism is no longer independent. It now depends on larger structures, such as markets and political interests. This article tries to map these two sides through the Anthony Giddens’s theoretical perspective, which puts journalism as a social agent and always confronts with other larger structures.